Covalent organic framework film as well as preparation method and application thereof
The preparation of covalent organic frame membranes through interface polymerization solves the problem of insufficient selectivity and antioxidant properties of nanofiltration membranes, achieves the effect of efficient removal of divalent ions, and improves the stability and applicability of the membrane.
Patent Information
- Application Number
- CN202411214683.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing nanofiltration membranes are difficult to improve selectivity while maintaining high throughput, and the poor antioxidant properties and limited structure of traditional polymer membrane materials limit the water treatment capacity. The nanopore size of covalent organic frame materials does not match the hydrated ions, limiting their application in water treatment.
Covalent organic frame membranes are prepared by interfacial polymerization, and the condensation reaction of polyaldehyde monomers and polyamine monomers is used to form an ordered pore structure, regulate the size and stacking behavior of the nanosheets, form a membrane with moderate pore size, and combine with strong covalent bonds. Improve the acid and alkali resistance and stability of the membrane.
It has achieved efficient removal of divalent ions in salt solution, with high ion selectivity and acid-base resistance, simplified the preparation process and a wide range of applications.
Smart Images

Figure CN119215679A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of separation membrane materials, and in particular to a covalent organic framework membrane and a preparation method and application thereof. Background Art
[0002] Membrane separation technology has been widely used in many fields such as food, medical, energy and water treatment due to its simple operation, high efficiency, energy saving and environmental friendliness. Nanofiltration is a membrane separation technology between ultrafiltration and reverse osmosis. The research on nanofiltration technology began in 1976, when JECadotte prepared piperazine polyamide membrane on polysulfone substrate. The pore size of nanofiltration membrane is roughly 0.5-2nm, and it shows higher selectivity for divalent and multivalent ions. Nanofiltration has the advantages of low operating pressure, high permeation flux and energy saving, which makes its operating cost more economical. Nanofiltration membranes are mainly divided into asymmetric membranes and composite membranes. The pore structure of asymmetric membranes brings high permeability, but at the same time, the regulation of the density of the cortex is often based on the sacrifice of flux, and it is restricted by a single membrane material, so it is difficult to improve the selectivity of asymmetric membranes while maintaining high flux. The mainstream nanofiltration membrane is a polyamide membrane, among which the interfacial polymerization reaction of diamine monomers and acyl chloride monomers is the most commonly used method for preparing polyamide membranes. Because the polyamide active layer has the characteristics of high cross-linking degree and negative surface charge, it can maintain high permeability while improving selectivity. However, the amide bonds produced by interfacial polymerization have poor antioxidant properties and are easily degraded by free chlorine. In addition, the choice of interfacial polymerization materials is generally limited to various diamines and trimesoyl chloride, and the resulting structures are more numerous but still relatively limited. In general, the development of water treatment membranes has been constrained by the inherent limitations of traditional membrane materials. Nanotechnology-supported water treatment membranes not only overcome the main challenges faced by traditional polymer membrane materials, but also provide new processing capabilities and solutions.
[0003] Covalent organic framework materials (COFs) are a class of crystalline porous polymers that can be completely pre-designed and controllably synthesized by covalent bonds. They have the characteristics of low mass density, high thermal stability, good physical and chemical stability and permanent porosity, and have been widely used in many fields such as catalysis, optoelectronics and separation. As separation membrane materials, covalent organic framework materials have the characteristics of high porosity, strong designability and excellent chemical stability, which is conducive to reducing mass transfer resistance and obtaining high permeability; by designing the structure of synthetic monomers, size screening and electrostatic repulsion mechanisms can be coupled simultaneously to obtain high selectivity. However, the intrinsic pore size of the nanopores of covalent organic framework materials is between 0.7 and 4.7 nm, which does not match the pore size of hydrated ions. In addition, the interlayer defects generated during the preparation of covalent organic framework membranes also limit their application in water treatment. Therefore, it is still difficult to develop covalent organic framework membranes that can achieve ion separation. Summary of the invention
[0004] The present disclosure provides a covalent organic framework membrane and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.
[0005] According to a first aspect of the present disclosure, a method for preparing a covalent organic framework film is provided, comprising the following steps:
[0006] S1: preparing an organic phase solution containing a polyaldehyde monomer and an aqueous phase solution containing a polyamine monomer;
[0007] S2: adding the organic phase solution of step S1 dropwise to the aqueous phase solution for reaction, and dialyzing the solution after the reaction to obtain a purified aqueous dispersion of covalent organic framework nanosheets;
[0008] S3: dispersing the aqueous dispersion of the covalent organic framework nanosheets in step S2, then filtering it onto a hydrophilic support, and performing heat treatment to solidify it to obtain the covalent organic framework membrane.
[0009] Specifically, the synthesis process of the covalent organic framework membrane is to form a covalent organic framework structure by condensing polyamine monomers and polyaldehyde monomers through interfacial polymerization. Since the covalent organic framework has an ordered pore structure of a specific size, the prepared membrane has the same uniform and ordered pore structure as the covalent organic framework material. By changing the dispersion composition of the covalent organic framework nanosheets, the size of the nanosheets and the stacking behavior of the nanosheets are regulated, so that the pore size of the covalent organic framework membrane is just between the monovalent and divalent hydrated ions, so that the divalent ions in the salt solution can be efficiently removed. In addition, the ordered and regular pore structure of the covalent organic framework material and its characteristics of being connected by strong covalent bonds give the covalent organic framework membrane acid and alkali resistance and high stability.
[0010] In one embodiment, the molar ratio of the polyaldehyde monomer to the polyamine monomer in step S1 is 2:3-5.
[0011] In a preferred embodiment, the molar ratio of the polyaldehyde monomer to the polyamine monomer in step S1 is 2:3.
[0012] In one embodiment, the polyaldehyde monomer is a small molecule containing a binary or polyaldehyde group in the structural formula, including glyoxal, glutaraldehyde, adipaldehyde, 1,3-butanedialdehyde, terephthalaldehyde, 2,5-dichloroterephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 1,4-dialdehyde-2,5-divinylbenzene, 2,3,5,6-tetrafluorobenzaldehyde, 2,5-dimethoxybenzene-1,4-dicarboxaldehyde, 4,4'-biphenyldicarboxaldehyde, 2,2'-bipyridine-5,5'-dicarboxaldehyde, 1,4-di(4-formaldehyde phenyl)benzene, 2,6-naphthalene dicarboxaldehyde, 1,10-phenanthroline-2,9-dicarboxaldehyde, At least one of 2,2'-bipyridine-4,4'-dicarboxaldehyde, 4-tert-butyl-2,6-formylphenol, 9,10-bis(4-formylphenyl)anthracene, trimesic acid aldehyde, 4-hydroxyisophthalic acid aldehyde, 2,4,6-triformylphloroglucinol, 1,3,5-tri(p-formylphenyl)benzene, tri(4-formylphenyl)amine, 2,4,6-tri(4-formylphenyl)-1,3,5-triazine, 3,3',5,5'-tetraformyl-4,4'-dihydroxybiphenyl, tetra(4-formylphenyl)silane, 1,3,6,8-tetra(4-formylphenyl)perylene, and tetra(4-formylphenyl)ethylene.
[0013] In one embodiment, the polyamine monomer is a small molecule or polymer containing a divalent or polyvalent primary or secondary amine group in the structural formula, including piperazine, p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, 1,4-diamino-2,5-divinylbenzene, 2,5-diaminopyridine, 5,5'-diamino-2,2'-bipyridine, m-phenylenediamine, o-phenylenediamine, 1,2,4,5-phenylenetetramine, biphenylenediamine and the like. derivatives, C2-C12 alkyl linear diamines and their derivatives, urea, oxalyl diamine, dithiooxalyl diamine, 2,5-diaminoterephthalic acid, 2-sulfonic acid-1,4-phenylenediamine, 2-isopropyl-1,4-phenylenediamine, 2,3,5,6-tetra(amino)benzoquinone, 4',5'-bis(4-aminophenyl)-[1,1':2',1"-terphenyl]-4,4"-diamine, 2, 4-diamino-6-phenyl-1,3,5-triazine, 5,10,15,20-tetrakis(4-aminophenyl)-21H, 23H-porphyrin, tetrakis(4-aminophenyl)ethylene, 1,2,4,5-tetrakis((4-aminophenyl)ethynyl)benzene, 3,3',4,4'-tetraaminobenzophenone, diethylenetriamine, dipropylenetriamine, dihexyltriamine, melamine, 1,3,5-triaminobenzene, 1 , at least one of 2,4-triaminobenzene, 2,6-diaminoanthracene, 4,4'-diaminoterphenyl, melem, p-diaminoazobenzene, 4,4,4,4-methylethanetetrayltetraphenylamine, 2,2-bis(4-aminophenyl)propane, hexa(4-aminobiphenyl)benzene, pyrazine-2,5-diamine, oxalic acid dihydrazide, succinic acid dihydrazide, tetrakis(4-aminophenyl)methane, polyethyleneimine, and polyethyleneamine.
[0014] In one embodiment, step S1 is to dissolve the polyaldehyde monomer in an organic solution to prepare the organic phase solution containing the polyaldehyde monomer.
[0015] Specifically, the organic solvent is selected from at least one of n-octanoic acid, 1,4-dioxane, mesitylene, ethanol, acetone, acetonitrile, n-hexane, n-heptane, ethyl acetate, dimethyl sulfoxide, and dichloromethane.
[0016] In one embodiment, in step S1, the polyamine monomer is dissolved in water to prepare the aqueous solution containing the polyamine monomer.
[0017] In one embodiment, the reaction conditions of step S2 are: temperature 20-25° C., time ≥ 72 h.
[0018] In a preferred embodiment, the reaction conditions in step S2 are: temperature 20° C., time 72 h.
[0019] In one embodiment, the dialysis process in step S2 includes: transferring the post-reaction solution into a dialysis bag, placing the dialysis bag in water for cleaning for ≥3 days, and the number of cleaning times is ≥3 times.
[0020] Specifically, after the dialysis in step S2, unreacted monomers can be removed, thereby obtaining a purified aqueous dispersion of the covalent organic framework nanosheets.
[0021] In one embodiment, the mass concentration of the covalent organic framework nanosheets in the aqueous dispersion of the covalent organic framework nanosheets is 0.1 to 5 g·L -1 .
[0022] In one possible implementation manner, step S3 uses a solvent to disperse the aqueous dispersion of the covalent organic framework nanosheets; the solvent is selected from a mixed solution of anhydrous ethanol and water, and the volume ratio of the anhydrous ethanol to the water is 1:0 to 0:1.
[0023] In one embodiment, the hydrophilic support is selected from a membrane prepared from at least one of hydrophilic polymers polysulfone, polyethersulfone, and polyacrylonitrile, and a membrane obtained by hydrophilizing at least one of polyethylene hydrophobic membrane and polyvinylidene fluoride hydrophobic membrane.
[0024] In one embodiment, the vacuum pressure of the filtration in step S3 is 0.02-0.05 MPa, and the time is 1-60 min.
[0025] Specifically, the aqueous dispersion of the dispersed covalent organic framework nanosheets is filtered onto a hydrophilic support to obtain a primary covalent organic framework membrane.
[0026] In one embodiment, the conditions for heat treatment curing in step S3 include: temperature 60-90° C., time 5-15 min.
[0027] According to a second aspect of the present disclosure, a covalent organic framework membrane prepared according to the above preparation method is provided.
[0028] According to a third aspect of the present disclosure, there is provided an application of the above covalent organic framework membrane, wherein the covalent organic framework membrane is used for removing divalent ions in a salt solution.
[0029] According to an implementable embodiment of the present disclosure, at least the following beneficial effects are achieved:
[0030] 1. The covalent organic framework membrane disclosed in the present invention has an ordered pore structure of a specific size and utilizes the electrostatic interaction of the charges carried by the framework to effectively remove divalent ions in the salt solution and has high ion selectivity.
[0031] 2. The covalent organic framework membrane disclosed in the present invention has the characteristics of strong covalent bond connection, which endows the covalent organic framework membrane with acid and alkali resistance and high stability.
[0032] 3. The preparation method of the covalent organic framework membrane disclosed in the present invention is simple, the preparation conditions are mild, and the application range is wide.
[0033] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:
[0035] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.
[0036] Figure 1 A schematic diagram of the process for preparing a covalent organic framework membrane disclosed in the present invention is shown;
[0037] Figure 2 The surface scanning electron microscope image of the covalent organic framework film 1 in Example 1 of the present disclosure is shown;
[0038] Figure 3 A cross-sectional scanning electron microscope image of the covalent organic framework membrane 1 in Example 1 of the present disclosure is shown;
[0039] Figure 4 The surface scanning electron microscope image of the covalent organic framework film 2 in Example 2 of the present disclosure is shown;
[0040] Figure 5 The surface scanning electron microscope image of the hydrophilized polyethylene film in Comparative Example 1 of the present disclosure is shown;
[0041] Figure 6 The Fourier transform attenuated total reflection infrared spectrum of the covalent organic framework film 1 and the COF nanosheet in Example 1 of the present disclosure is shown;
[0042] Figure 7 The Fourier transform attenuated total reflection infrared spectra of the hydrophilized polyethylene film and the original commercial polyethylene film in Comparative Example 1 of the present disclosure are shown;
[0043] Figure 8 The 64h long-term test performance diagram of the covalent organic framework membrane 1 in Example 1 of the present disclosure is shown. DETAILED DESCRIPTION
[0044] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.
[0045] The present disclosure provides a method for preparing a covalent organic framework membrane, the flow chart of which is as follows: Figure 1 As shown. Specifically including the following steps:
[0046] S1: preparing an organic phase solution containing a polyaldehyde monomer and an aqueous phase solution containing a polyamine monomer;
[0047] S2: adding the organic phase solution prepared in step S1 dropwise to the aqueous phase solution for reaction (using interfacial polymerization to allow the polyamine monomer and the polyaldehyde monomer to undergo condensation reaction), dialyzing the solution after the reaction to obtain a purified aqueous dispersion of covalent organic framework (COF) nanosheets;
[0048] S3: dispersing the aqueous dispersion of the covalent organic framework nanosheets obtained in step S2, then filtering it onto a hydrophilic support, and performing heat treatment to solidify it to obtain a covalent organic framework membrane.
[0049] There is no particular limitation on the sources of all raw materials in the present disclosure and the following examples, and any raw materials may be commercially available.
[0050] The method for detecting water permeation flux in the embodiment of the present disclosure is as follows:
[0051] The membrane permeation selectivity performance test system made in the laboratory was used to test the water permeation flux and salt retention rate of the membrane. The test system consists of pumps, membrane tanks, pipelines, regulating valves, pressure and flow detectors, etc. The effective membrane area tested was 4.9 cm 2 , the test pressure is 5 bar and the test temperature is 25±0.5℃.
[0052] The calculation formula of water permeation flux is as follows: J = V / [A*Δt];
[0053] Where J is the water permeation flux of the membrane (L m -2 h -1 ), V is the permeate volume (L), A is the membrane effective area (m 2 ), Δt is the penetration time (s).
[0054] The calculation formula of interception rate is as follows: R = (1-C p / C f )*100%;
[0055] Among them, C p is the concentration of the permeate (g L -1 ), C f is the concentration of the raw material solution (g L -1 ).
[0056] Salt concentration in retention rate test: NaCl, MgCl2, Na2SO4 and MgSO4 are all 1 g L -1 .
[0057] Example 1
[0058] In this embodiment, a covalent organic framework membrane 1 is prepared, and the specific process is as follows:
[0059] (1) 20 mM 1,3,5-trialdehyde pyrogallol was dissolved in 20 mL of octanoic acid to prepare an organic phase solution containing a polyaldehyde monomer, and 30 mM 2,5-diaminobenzenesulfonic acid was dissolved in 30 mL of deionized water to prepare an aqueous phase solution containing a polyamine monomer, and each solution was ultrasonicated for 30 min.
[0060] (2) Gently drip the organic phase solution of step (1) onto the aqueous phase solution and react in a thermostat at 20° C. for 72 hours. Transfer the solution after the reaction (the aqueous phase solution at the bottom) to a dialysis bag, and place the dialysis bag in a beaker containing 1 L of deionized water for cleaning for 3 days, changing the water at least once a day to remove unreacted monomers, thereby obtaining a purified aqueous dispersion of covalent organic framework nanosheets.
[0061] (3) Take 1 mL of the aqueous dispersion of the covalent organic framework nanosheets prepared in step (2) and dilute it to 20 mL with anhydrous ethanol to make it evenly dispersed. Then use a filtration device with a diameter of 8 cm to filter it onto a hydrophilized polyethylene (PE) support. The vacuum pressure during the filtration process is 0.02 MPa and the filtration time is 1 hour. The obtained primary covalent organic framework membrane is heat-treated and cured in an oven at 60°C for 15 minutes, and finally the covalent organic framework membrane 1 is successfully synthesized.
[0062] The test results show that the rejection rates of covalent organic framework membrane 1 for Na2SO4, MgSO4, MgCl2 and NaCl are 98.83%, 93.06%, 61.46% and 77.65% respectively; the water permeation flux is 4.35 L m -2 h -1 The membrane can maintain stable separation performance during 64h continuous operation.
[0063] Figure 2 This is the surface scanning electron microscope image of the covalent organic framework membrane 1. Figure 2 It shows that the surface of the covalent organic framework film 1 is smooth, dense and defect-free. Figure 3This is a cross-sectional scanning electron microscope image of the covalent organic framework membrane 1. Figure 3 It is shown that the thickness of the selective separation layer of the covalent organic framework membrane 1 is about 137 nm. Figure 6 This is the Fourier transform attenuated total reflection infrared spectra of the covalent organic framework film 1 and the covalent organic framework (COF) nanosheet. It can be seen that the characteristic peaks of the covalent organic framework film 1 and the COF nanosheet are basically consistent. Figure 8 This is the 64h long-term test performance diagram of the covalent organic framework membrane 1. It can be seen that during the 64h test, the permeation flux and retention rate of the covalent organic framework membrane 1 remain basically unchanged, indicating that it has good stability.
[0064] Example 2
[0065] In this embodiment, a covalent organic framework membrane 2 is prepared, and the specific process is as follows:
[0066] (1) 20 mM 1,3,5-trialdehyde pyrogallol was dissolved in 20 mL of octanoic acid to prepare an organic phase solution containing a polyaldehyde monomer, and 30 mM 2,5-diaminobenzenesulfonic acid was dissolved in 30 mL of deionized water to prepare an aqueous phase solution containing a polyamine monomer, and each solution was ultrasonicated for 30 min.
[0067] (2) Gently drip the organic phase solution of step (1) onto the aqueous phase solution and react in a thermostat at 20° C. for 72 hours. Transfer the solution after the reaction (the aqueous phase solution at the bottom) to a dialysis bag, and place the dialysis bag in a beaker containing 1 L of deionized water for cleaning for 3 days, changing the water at least once a day to remove unreacted monomers, thereby obtaining a purified aqueous dispersion of covalent organic framework nanosheets.
[0068] (3) Take 1 mL of the aqueous dispersion of the covalent organic framework nanosheets prepared in step (2) and dilute it to 20 mL with deionized water to make it evenly dispersed. Then use a filtration device with a diameter of 8 cm to filter it onto a hydrophilized polyethylene (PE) support. The vacuum pressure during the filtration process is 0.02 MPa and the filtration time is 1 hour. The obtained primary covalent organic framework membrane is heat-treated and cured in an oven at 60°C for 15 minutes, and finally the covalent organic framework membrane 2 is successfully synthesized.
[0069] The test results show that the rejection rates of covalent organic framework membrane 2 for Na2SO4, MgSO4, MgCl2 and NaCl are 89.33%, 76.00%, 34.19% and 52.83% respectively; the water permeation flux is 8.43 L m -2 h -1 .
[0070] Figure 4 This is a surface scanning electron microscope image of the covalent organic framework membrane 2. Figure 4It is shown that the surface of the covalent organic framework film 2 has uneven defects, which may be due to the small size of the covalent organic framework nanosheets in water, causing the nanosheets to be embedded in the support instead of covering the support.
[0071] Example 3
[0072] In this embodiment, a covalent organic framework film 3 is prepared, and the specific process is as follows:
[0073] (1) 20 mM 1,3,5-trialdehyde pyrogallol was dissolved in 20 mL of octanoic acid to prepare an organic phase solution containing a polyaldehyde monomer, and 30 mM 2,5-diaminobenzenesulfonic acid was dissolved in 30 mL of deionized water to prepare an aqueous phase solution containing a polyamine monomer, and each solution was ultrasonicated for 30 min.
[0074] (2) Gently drip the organic phase solution of step (1) onto the aqueous phase solution and react in a thermostat at 20° C. for 72 hours. Transfer the solution after the reaction (the aqueous phase solution at the bottom) to a dialysis bag, and place the dialysis bag in a beaker containing 1 L of deionized water for cleaning for 3 days, changing the water at least once a day to remove unreacted monomers, thereby obtaining a purified aqueous dispersion of covalent organic framework nanosheets.
[0075] (3) Take 0.25 mL of the aqueous dispersion of the covalent organic framework nanosheets prepared in step (2), dilute it to 20 mL with anhydrous ethanol, and evenly disperse it. Then use a filtration device with a diameter of 8 cm to filter it onto a hydrophilized polyethylene (PE) support. The vacuum pressure during the filtration process is 0.02 MPa, and the filtration time is 1 hour. The obtained primary covalent organic framework membrane is heat-treated and cured in an oven at 60°C for 15 minutes, and finally the covalent organic framework membrane 3 is successfully synthesized.
[0076] The test results show that the rejection rates of covalent organic framework membrane 3 for Na2SO4, MgSO4, MgCl2 and NaCl are 76.64%, 70.43%, 36.07% and 73.54% respectively; the water permeation flux is 14.85 L m -2 h -1 .
[0077] Comparative Example 1
[0078] This comparative example prepares a hydrophilic polyethylene membrane, which is different from Example 1 in that the membrane prepared in this comparative example does not contain a covalent organic framework. The specific process is as follows:
[0079] Dissolve 0.05g of polyvinyl alcohol in 100mL of deionized water at 95°C, stir continuously for 8h, then cool to room temperature, and mix the polyvinyl alcohol aqueous solution with anhydrous ethanol in a volume ratio of 1:1. Subsequently, add 1mL of glutaraldehyde, 5mL of concentrated sulfuric acid and 5mL of acetic acid, respectively, mix and stir at room temperature for 1h to obtain a polyvinyl alcohol / glutaraldehyde solution. Soak the commercial polyethylene support in the polyvinyl alcohol / glutaraldehyde solution at room temperature for 1h. After the cross-linking reaction, remove the excess polyvinyl alcohol / glutaraldehyde solution on the support with an air knife. The polyethylene support is further thermally cured at 90°C for 10min to complete the hydrophilic modification of the polyethylene support and obtain a hydrophilic polyethylene membrane without a covalent organic framework.
[0080] The test results show that the retention rates of the hydrophilic polyethylene membrane for Na2SO4, MgSO4, MgCl2 and NaCl are 11.61%, 15.98%, 11.24% and 12.86% respectively; the water permeation flux is 356.73Lm -2 h -1 .
[0081] Figure 5 This is a scanning electron micrograph of the surface of the hydrophilized polyethylene membrane. Figure 5 It shows that the surface of the membrane is rough and has a large number of defects. The pores in some defects are large and there is no ordered pore structure, resulting in a low retention rate for divalent ions in salt solutions and a high permeability flux for water. Figure 7 The following is the Fourier transform attenuated total reflection infrared spectra of the hydrophilized polyethylene film prepared in this comparative example and the original commercial polyethylene film. It can be seen that after being modified with polyvinyl alcohol, the surface of the hydrophilized polyethylene film has a high -1 The characteristic peaks of hydroxyl groups appeared on the left and right, which proved that the hydrophilicity of the polyethylene film was improved, which would be beneficial to enhance the hydrogen bonding force between the polyethylene film and the COF nanosheets.
[0082] Comparative Example 2
[0083] This comparative example prepared a covalent organic framework membrane 4. The difference from Example 1 is that this comparative example did not use a hydrophilic support, but used an original commercial polyethylene support. The specific process is as follows:
[0084] (1) 20 mM 1,3,5-trialdehyde pyrogallol was dissolved in 20 mL of octanoic acid to prepare an organic phase solution containing a polyaldehyde monomer, and 30 mM 2,5-diaminobenzenesulfonic acid was dissolved in 30 mL of deionized water to prepare an aqueous phase solution containing a polyamine monomer, and each solution was ultrasonicated for 30 min.
[0085] (2) Gently drip the organic phase solution of step (1) onto the aqueous phase solution and react in a thermostat at 20° C. for 72 hours. Transfer the solution after the reaction (the aqueous phase solution at the bottom) to a dialysis bag, and place the dialysis bag in a beaker containing 1 L of deionized water for cleaning for 3 days, changing the water at least once a day to remove unreacted monomers, thereby obtaining a purified aqueous dispersion of covalent organic framework nanosheets.
[0086] (3) Take 1 mL of the aqueous dispersion of the covalent organic framework nanosheets prepared in step (2) and dilute it to 20 mL with anhydrous ethanol to make it evenly dispersed. Then use a filtration device with a diameter of 8 cm to filter it onto the original commercial polyethylene (PE) support. The vacuum pressure during the filtration process is 0.02 MPa and the filtration time is 1 hour. The obtained primary covalent organic framework membrane is heat-treated and cured in an oven at 60°C for 15 minutes, and finally the covalent organic framework membrane 4 is successfully synthesized.
[0087] The test results show that the rejection rates of covalent organic framework membrane 4 for Na2SO4, MgSO4, MgCl2 and NaCl are 32.23%, 31.76%, 22.91% and 25.61% respectively; the water permeation flux is 19.7 L m -2 h -1 .
[0088] The specific implementation methods and results of the above examples and comparative examples are shown in Table 1.
[0089] Table 1
[0090]
[0091] It can be seen from Table 1 that the covalent organic framework membrane (ie, the covalent organic framework membrane 1 of Example 1) obtained by self-assembly assisted by anhydrous ethanol on a hydrophilized polyethylene support has a higher desalination performance.
[0092] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution of this disclosure can be achieved, and this document is not limited here.
[0093] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0094] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for preparing a covalent organic framework membrane, characterized in that: The following steps are involved: S1: preparing an organic phase solution containing a polyaldehyde monomer and an aqueous phase solution containing a polyamine monomer; S2: adding the organic phase solution of step S1 dropwise to the aqueous phase solution for reaction, and dialyzing the solution after the reaction to obtain a purified aqueous dispersion of covalent organic framework nanosheets; S3: dispersing the aqueous dispersion of the covalent organic framework nanosheets in step S2, then filtering it onto a hydrophilic support, and performing heat treatment to solidify it to obtain the covalent organic framework membrane.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the polyaldehyde monomer to the polyamine monomer is 2:3-5; Preferably, the polyaldehyde monomer is a small molecule containing a binary or polyaldehyde group in the structural formula, including glyoxal, glutaraldehyde, adipaldehyde, 1,3-butanedialdehyde, terephthalaldehyde, 2,5-dichloroterephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 1,4-dialdehyde-2,5-divinylbenzene, 2,3,5,6-tetrafluorobenzaldehyde, 2,5-dimethoxybenzene-1,4-dicarboxaldehyde, 4,4'-biphenylcarboxaldehyde, 2,2'-bipyridine-5,5'-carboxaldehyde, 1,4-di(4-formaldehydephenyl)benzene, 2,6-naphthalene dicarboxaldehyde, 1,10-phenanthroline-2,9-carboxaldehyde, 2,2 At least one of '-bipyridine-4,4'-dicarboxaldehyde, 4-tert-butyl-2,6-formylphenol, 9,10-bis(4-formylphenyl)anthracene, trimesicaldehyde, 4-hydroxyisophthalicaldehyde, 2,4,6-triformylphloroglucinol, 1,3,5-tri(p-formylphenyl)benzene, tri(4-formylphenyl)amine, 2,4,6-tri(4-formylphenyl)-1,3,5-triazine, 3,3',5,5'-tetraformyl-4,4'-dihydroxybiphenyl, tetra(4-formylphenyl)silane, 1,3,6,8-tetra(4-formylphenyl)perylene, and tetra(4-formylphenyl)ethylene; Preferably, the polyamine monomer is a small molecule or polymer containing a divalent or polyvalent primary or secondary amine group in the structural formula, including piperazine, p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, 1,4-diamino-2,5-divinylbenzene, 2,5-diaminopyridine, 5,5'-diamino-2,2'-bipyridine, m-phenylenediamine, o-phenylenediamine, 1,2,4,5-phenylenetetramine, biphenylenediamine and its derivatives, C2-C12 alkyl linear diamines and their derivatives, urea, oxalyl diamine, dithiooxalyl diamine, 2,5-diaminoterephthalic acid, 2-sulfonic acid-1,4-phenylenediamine, 2-isopropyl-1,4-phenylenediamine, 2,3,5,6-tetrakis(amino)benzoquinone, 4',5'-bis(4-aminophenyl)-[1,1':2',1"-terphenyl]-4,4"-diamine, 2,4- Diamino-6-phenyl-1,3,5-triazine, 5,10,15,20-tetrakis(4-aminophenyl)-21H, 23H-porphyrin, tetrakis(4-aminophenyl)ethylene, 1,2,4,5-tetrakis((4-aminophenyl)ethynyl)benzene, 3,3',4,4'-tetraaminobenzophenone, diethylenetriamine, dipropylenetriamine, dihexyltriamine, melamine, 1,3,5-triaminobenzene, 1, At least one of 2,4-triaminobenzene, 2,6-diaminoanthracene, 4,4'-diaminoterphenyl, melem, p-diaminoazobenzene, 4,4,4,4-methylethanetetrayltetraphenylamine, 2,2-bis(4-aminophenyl)propane, hexa(4-aminobiphenyl)benzene, pyrazine-2,5-diamine, oxalic acid dihydrazide, succinic acid dihydrazide, tetrakis(4-aminophenyl)methane, polyethyleneimine, and polyethyleneamine.
3. The preparation method according to claim 1, characterized in that: Step S1: dissolving the polyaldehyde monomer in an organic solution to prepare the organic phase solution containing the polyaldehyde monomer; the organic solution is selected from at least one of n-octanoic acid, 1,4-dioxane, mesitylene, ethanol, acetone, acetonitrile, n-hexane, n-heptane, ethyl acetate, dimethyl sulfoxide, and dichloromethane; Preferably, in step S1, the polyamine monomer is dissolved in water to prepare the aqueous phase solution containing the polyamine monomer.
4. The preparation method according to claim 1, characterized in that: The reaction conditions of step S2 are: temperature 20-25° C., time ≥ 72 h; Preferably, the dialysis process in step S2 comprises: transferring the reacted solution into a dialysis bag, placing the dialysis bag in water for cleaning for ≥3 days, and the number of cleaning times is ≥3 times.
5. The preparation method according to claim 1, characterized in that: In the aqueous dispersion of the covalent organic framework nanosheets, the mass concentration of the covalent organic framework nanosheets is 0.1 to 5 g·L -1 .
6. The preparation method according to claim 1, characterized in that: Step S3 uses a solvent to disperse the aqueous dispersion of the covalent organic framework nanosheets; the solvent is selected from a mixed solution of anhydrous ethanol and water, and the volume ratio of the anhydrous ethanol to the water is 1:0 to 0:
1.
7. The preparation method according to claim 1, characterized in that: The hydrophilic support is selected from a membrane prepared from at least one of hydrophilic polymers polysulfone, polyethersulfone and polyacrylonitrile, and a membrane obtained by hydrophilic modification of at least one of polyethylene hydrophobic membrane and polyvinylidene fluoride hydrophobic membrane.
8. The preparation method according to claim 1, characterized in that: The vacuum pressure of the filtration in step S3 is 0.02-0.05 MPa, and the time is 1-60 min; Preferably, the conditions for heat treatment curing in step S3 include: temperature 60-90° C., time 5-15 min.
9. The covalent organic framework membrane prepared according to the preparation method according to any one of claims 1 to 8.
10. The use of the covalent organic framework membrane according to claim 9, characterized in that: The covalent organic framework membrane is used for removing divalent ions in a salt solution.
Citation Information
Cited By
Method for rapidly preparing imine covalent organic framework film and application of imine covalent organic framework film
CN120242789A
Hierarchical pore COF membrane based on pillararene as well as preparation method and application of hierarchical pore COF membrane
CN120437840A
Hierarchical COF membrane based on pillararomatic hydrocarbons and its preparation method and application
CN120437840B
Preparation method and photocatalytic application of heterogeneous covalent organic framework film
CN120571434A
Preparation method of a heterogeneous covalent organic framework film and photocatalytic application thereof
CN120571434B
